PERAN KINERJA PENYULUH DAN EFEKTIVITAS PELAKSANAAN PENYULUHAN PADA PROGRAM INTENSIFIKASI JAGUNG - Rahmawati Rahmawati; Mahludin Baruwadi; Mohamad Ikbal Bahua (Jurnal Sosial Ekonomi Pertanian, 2019)
The purpose of this research it is analyzing the role of extension performance and the effectiveness of the agricultural extension on corn intensification program. The object of this research is extension agricultural who conducted the program intensification of corn. Research undertaken in Gorontalo Utara Regency of November 2018 until January 2019. Research methodology is descriptive quantitative analysis by the use of research semantic differential. The results of the study showed that the role of the performance of agricultural extension on corn intensification program was instrumental good with an average interval 44,77 that acts as motivator, facilitators, educator, and the communicators in the implementation of the corn intensification program. While the implementation of agricultural extension services on the program intensification corn is very effective with rata-rata scales intervals 23,95 adapted to the intensification of phases of the program from provision of corn seed until after the harvest.